Correlation and Path analysis in Barley (Hordeum vulgare L.) for yield and contributing traits under varied conditions - Manhas, Neha; Kashyap, Subhash Chander (Journal of Cereal Research, 2023)
The present experiment was carried out for evaluation of seventeen barley (Hordeum vulgare L.) genotypes for grain yield and its contributing characters in four environments. The experiment was conducted at two locations viz., Advance Centre for Rainfed Agriculture SKUAST-Jammu, Dhiansar (under rainfed condition) and Research Farm Chatha, Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu (under irrigated condition) during Rabi 2019-20 and 2020-21, in Randomized Block Design with three replications. The data was recorded on characters viz. days to 50 per cent flowering, plant height (cm), chlorophyll content of leaf (SPAD values), flag leaf length (cm), flag leaf width (cm), number of tillers per plant, spike length (cm), number of spikelets per spike, number of grains per spike, biological yield/plant (g), grain yield/plant (g), test weight (g) and harvest index (%). Significant and positive correlation of grain yield per plant was observed with harvest index, number of grains per spike, plant height and flag leaf width at both genotypic and phenotypic levels. Positive and direct effect on grain yield was observed through harvest index, number of tillers per plant, plant height, SPAD values, days to 50% flowering at both genotypic and phenotypic levels in pooled environment. This experiment concluded that the characters, harvest index, number of tillers per plant, plant height, SPAD values, days to 50% flowering revealed true relationship between these characters and grain yield per plant, thus direct selection would be considered for grain yield improvement for these traits.